Statistical methods in psychiatry research and SPSS - Reddy, M. Venkataswamy (Oakville, ON : Apple Academic Press Inc., 2019)
This volume, Statistical Methods in Psychiatry Research and SPSS, now going into its second edition, has been helping psychiatrists expand their knowledge of statistical methods and fills the gaps in their applications as well as introduces data analysis software. It addresses the statistical needs of physicians and presents a simplified approach. The book emphasizes the classification of fundamental statistical methods in psychiatry research that are precise and simple. Professionals in the field of mental health and allied subjects without any mathematical background will easily understand all the relevant statistical methods and carry out the analysis and interpret the results in their respective field without consulting any statistician. This new volume has over 100 pages of new material, including several new appendixes. The sequence of the chapters, the sections within the chapters, the subsections within the sections, and the points within the subsections have all been arranged to help professionals in classification refine their knowledge in statistical methods and fills the gaps.
Psychiatric research -- Observational studies -- Experimental studies -- One-variable descriptive statistics -- Mental health statistics -- Probability and probability distributions -- Sampling theory and methods -- Basic elements of statistical inference -- Parametric tests of significance -- Experimental data analysis : ANOVA -- Non-parametric tests of significance -- Correlation analysis and regression analysis -- Reliability analysis and validity analysis -- Survival analysis and time series analysis -- Multivariate statistical methods -- Cluster analysis -- Discriminant analysis -- Factor analysis -- Meta-analysis -- Reporting the results -- Statistical package for social sciences -- Running data analysis using SPSS.
OCLC-licensed vendor bibliographic record.
Keywords: SPSS (Computer file); Psychiatry -- Research -- Statistical methods; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; COMPUTERS / Mathematical & Statistical Software; MEDICAL / Administration; MEDICAL / Physician & Patient